2015
DOI: 10.5194/bg-12-5981-2015
|View full text |Cite
|
Sign up to set email alerts
|

Interdependencies between temperature and moisture sensitivities of CO<sub>2</sub> emissions in European land ecosystems

Abstract: Abstract. Soil respiration is one of the largest terrestrial fluxes of carbon dioxide (CO 2 ) to the atmosphere. Hence, small changes in soil respiration rates could have large effects on atmospheric CO 2 . In order to assess CO 2 emissions from diverse European soils with different land-use types and climate (soil moisture and temperature), we conducted a laboratory incubation experiment.Emission measurements of CO 2 under controlled conditions were conducted using soil monoliths of nine sites from a European… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Soil temperature explained most of the variability (47%) of soil respiration across land use types, with an additional 13% explained by soil moisture and bulk density, which confirms the findings of several previous studies on the controls of soil CO 2 respiration in terrestrial ecosystems (Carter et al, 2012;Gritsch et al, 2015;Imer et al, 2013;Luo et al, 2012;Schaufler et al, 2010;Skiba et al, 2013). The temperature dependence of soil respiration can be explained by the stimulation of biological activity (plant roots and microbial communities) with increasing temperature, and this was evident within all the investigated land use types as indicated by the MLR analysis (Table 2).…”
Section: Carbon Dioxide Fluxessupporting
confidence: 87%
See 1 more Smart Citation
“…Soil temperature explained most of the variability (47%) of soil respiration across land use types, with an additional 13% explained by soil moisture and bulk density, which confirms the findings of several previous studies on the controls of soil CO 2 respiration in terrestrial ecosystems (Carter et al, 2012;Gritsch et al, 2015;Imer et al, 2013;Luo et al, 2012;Schaufler et al, 2010;Skiba et al, 2013). The temperature dependence of soil respiration can be explained by the stimulation of biological activity (plant roots and microbial communities) with increasing temperature, and this was evident within all the investigated land use types as indicated by the MLR analysis (Table 2).…”
Section: Carbon Dioxide Fluxessupporting
confidence: 87%
“…Global methane emission controls include soil moisture or water table depth, soil carbon content, soil temperature and pH, and vegetation composition (Carter et al, 2012;Levy et al, 2012;Turetsky et al, 2014), but the relative importance of these controls varies depending on the spatial and temporal scales investigated (Dise, 1993;Levy et al, 2012) and also the ecosystem type. Soil temperature and moisture are also postulated as universal controls of respiratory CO 2 production across ecosystems (Gritsch, Zimmermann, & Zechmeister-Boltenstern, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These fixed Q 10 values are widely used in ecosystem models (Foereid et al, ; Mahecha et al, ; Potter et al, ). Conversely, several studies have suggested that Q 10 is variable, with values ranging from 1 to more than 12 (Gritsch et al, ; Hamdi et al, ) and reaching 4.5 in Arctic tundra ecosystems (Ueyama et al, ). Globally, Q 10 seems to be amplified in Arctic ecosystems in comparison to temperate and tropical regions, perhaps due to an inverse correlation with mean annual temperature across biomes (Bekku et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…After pre-incubation at 4°C for 6 days, soil samples were sequentially set to 5°C, 10°C, 15°C, 20°C, and 25°C by controlling the temperature of the water bath of the Respicond system. Samples were kept at each temperature for 24 h (see also Gritsch et al 2015). The first 12 h after each temperature rise were treated as equilibration time.…”
Section: Methodsmentioning
confidence: 99%
“…The authors criticized that sample preprocessing like sieving and storage might alter microbial biomass, microbial activity, microbial community composition, and the availability of substrate. However, storage is mostly inevitable for practical reasons (e.g., Gritsch et al 2015;Lefèvre et al 2014;Meyer et al 2017) and sieving (mostly to < 2 mm) is a common practice to remove roots, plant residues, and rock fragments and to ensure homogenization of the soil (e.g., Conant et al 2008;Fierer et al 2006;Wang et al 2016). Only few studies on Q10 were conducted using undisturbed and/or fresh samples (e.g., Miller and Geisseler 2018;Reichstein et al 2005) An alteration of SR and Q10 by sieving and storage might be straightforward if all soils were similarly affected.…”
Section: Introductionmentioning
confidence: 99%